AmgRS‐mediated envelope stress‐inducible expression of the mexXY multidrug efflux operon of Pseudomonas aeruginosa. Issue 1 (1st December 2014) - Lau, Calvin Ho‐Fung; Krahn, Thomas; Gilmour, Christie; Mullen, Erin; Poole, Keith
Abstract AmgRS is an envelope stress‐responsive two‐component system and aminoglycoside resistance determinant in Pseudomonas aeruginosa that is proposed to protect cells from membrane damage caused by aminoglycoside‐generated mistranslated polypeptides. Consistent with this, a ΔamgR strain showed increased aminoglycoside‐promoted membrane damage, damage that was largely absent in AmgRS‐activated amgS‐mutant strains. Intriguingly, one such mutation, V121G, while providing for enhanced resistance to aminoglycosides, rendered P. aeruginosa susceptible to several ribosome‐targeting nonaminoglycoside antimicrobials that are inducers and presumed substrates of the MexXY‐OprM multidrug efflux system. Surprisingly, the amgSV121G mutation increased mexXY expression threefold, suggesting that export of these nonaminoglycosides was compromised in the amgSV121G mutant. Nonetheless, a link was established between AmgRS activation and mexXY expression and this was confirmed in studies showing that aminoglycoside‐promoted mexXY expression is dependent on AmgRS. While nonaminoglycosides also induced mexXY expression, this was not AmgRS‐dependent, consistent with these agents not generating mistranslated polypeptides and not activating AmgRS. The aminoglycoside inducibility of mexXY was abrogated in a mutant lacking the AmgRS target genes htpX and PA5528, encoding a presumed cytoplasmic membrane‐associated protease and a membrane protein of unknown function, respectively. Thus, aminoglycoside induction of mexXY is a response to membrane damage and activation of the AmgRS two‐component system.